2009
DOI: 10.1017/s1368980009991285
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of BMI and family history on diabetes: the Humboldt Study

Abstract: Objective: To examine the joint effect of family history and BMI on diabetes. Design: Cross-sectional study. Setting: A rural community in Saskatchewan, Canada. Subjects: The analysis was based on data from 2081 adults, 18-79 years of age, who participated in the Humboldt Study conducted in 2003. Doctor-diagnosed diabetes and family history of diabetes of biological parents and siblings were self-reported. Body weight and height were objectively measured. The interaction of family history and BMI on diabetes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…However, BMI may also be influenced by genes indicating the possibility that also gene-gene interactions may contribute to our findings. The observation of an interaction between a parental history of diabetes and obesity concurs with results from a Canadian study, also cross-sectional in its design, suggesting that the combination of high BMI and a family history of diabetes increases the risk to develop diabetes [17]. However, the analyses were performed on men and women combined.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, BMI may also be influenced by genes indicating the possibility that also gene-gene interactions may contribute to our findings. The observation of an interaction between a parental history of diabetes and obesity concurs with results from a Canadian study, also cross-sectional in its design, suggesting that the combination of high BMI and a family history of diabetes increases the risk to develop diabetes [17]. However, the analyses were performed on men and women combined.…”
Section: Discussionsupporting
confidence: 80%
“…Analyses of interactions between family history and different environmental factors may thus identify environmental factors that if combined with a genetic susceptibility are particularly hazardous with regard to diabetes. Only a few earlier studies have evaluated interaction effects for the combination of family history of diabetes and presence of risk factors related to lifestyle and results are divergent [12], [17].…”
Section: Introductionmentioning
confidence: 99%
“…These results, which need to be replicated in different samples, extend previous research showing that additional risk factors such as obesity work interactively with parental history of diabetes (8, 9, 11) to influence risk for type 2 diabetes. Current etiological understanding of diabetes suggests that underlying genetic risk is compounded by other factors until clinical threshold is reached (4).…”
Section: Discussionsupporting
confidence: 80%
“…In our study, we found a joint effect of FHD and abdominal obesity on IFG. Consistently, studies from Canadian and Finnish populations have shown joint effects of family history and obesity on diabetes [24,23]. Adjusted for age, sex, region, marital status, education level, occupation, smoking, drinking, physical activity, sleep quality, and history of hypertension.…”
Section: Discussionmentioning
confidence: 67%
“…The MONICA/KORA Augsburg cohort study reported an additive effect of overall and abdominal obesity on diabetes [22]. Joint effects of genetic risk scores and obesity had been reported to have contributed to the risk of diabetes [23,24]. Abdominal obesity was classified as waist circumference ≥85 cm for men and ≥80 cm for women.…”
Section: Discussionmentioning
confidence: 99%